The 2022 report of the Lancet Countdown on health and climate change: health at the mercy of fossil fuels - Romanello, Marina; Rocklöv, Joacim (The lancet, 2022)
Extreme heat exposure has been associated with hypertension. However, its interactive influences with air pollution, green and blue spaces are unclear. This study aimed to explore the interaction between heatwaves, air pollution, green and blue spaces on hypertension. Cohort data enrolled 6448 Chinese older adults aged 65 years and over were derived from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) between 2008 and 2018. Nine heatwave definitions, combining three heat thresholds (92.5th, 95th, and 97.5th percentiles of daily maximum temperature) and three durations (≥2, 3 and 4 days) were used as time-varying variables in the analysis and were the one-year exposure before survival events. Fine particulate matter (PM ≤2.5 μm in aerodynamic diameter (PM2.5)), the Normalized Difference Vegetation Index (NDVI) and the average proportion of open water bodies were used to reflect the air pollution, green and blue space exposures, respectively. PM2.5, green and blue space exposures were time-varying indicators and contemporaneous with heatwaves. Mixed Cox models with time-varying variables were fitted to assess the multiplicative and additive interaction of heatwaves, PM2.5, and green and blue spaces on hypertension, measured by a traditional product term with the ratio of hazard ratio (HR) and relative risk due to interaction (RERI), respectively. A positive multiplicative (HRs >1) and additive interaction (RERIs >0) between heatwaves and higher PM2.5 levels was observed. There was a synergistic effect between heatwaves and decreasing greenness levels on hypertension incidence on additive and multiplicative scales. No significant interaction between heatwaves and blue space was observed in the analysis. The combined effects of heatwaves, air pollution, green and blue space exposures on the risk of hypertension varied with age, gender, and educational attainment. This study's findings complemented the existing evidence and revealed synergistic harmful impacts for heatwaves with air pollution and lack of green space on hypertension incidence. - The informal economy is crucial for making cities function, and it provides the main means of income for a significant proportion of all workers globally. At the same time, informal workers are extremely vulnerable to the effects of climate change, with higher temperatures and more intense weather events causing direct physical harm and contributing to ill-health. This paper analyzes research from three cities in India and Zimbabwe (Indore, Harare, and Masvingo) to describe the vulnerability of informal workers in several sectors. It highlights the ways in which the direct impacts of climate change are compounded by other factors, including low-quality living conditions and the absence of provision for Occupational Health and Safety (OHS). Informal workers in the three cities have adopted a range of responses to reduce risk, and there are some recent inclusive engagements with local officials to enhance living and working conditions. However, key interventions such as expanding access to social protection (which has important potential to foster climate resilience) often fail to reach the most vulnerable urban informal workers. We conclude with recommendations and an agenda for more equitable policy and practice that can support multiple benefits for informal workers' health, livelihoods, and climate resilience in urban areas. - We are facing socio-ecological crises and failing to meet the basic needs of everyone in society whilst living within planetary boundaries. These interconnected problems are complex, which require urgent transdisciplinary efforts informed by theories of change. How can we address this in cities in a way that is equitable and sustainable, since cities are complex, dynamic ecosystems with interdependent relationships? What processes, dynamics and determinants are involved? What and how are local policies designed and implemented with the intention of achieving sustainable wellbeing for all? How do normative competences shape cities' capacities to directly respond to social and ecological needs? How can we effectively assess and compare advancements being made in different cities? Given this complexity, more systemic, integrated, and theoretical understanding is needed. We present a new conceptual framework which aims to strengthen understanding of the processes, dimensions, determinants, bi-directional relations and dynamics that influence the opportunities for cities to become more equitable and sustainable. The framework places a specific emphasis on political determinants, and can serve as a tool to guide public policy design and evaluation, and monitoring of the progress made across the various dimensions of sustainability wellbeing for all in different urban contexts. - In the context of accelerating concern regarding the climate and ecological crisis and the recognition of this crisis as a health threat, there is growing motivation among the health-care community to reduce the negative environmental impact of health care. Globally, the health-care sector is estimated to be the 5th largest carbon emitter. A health system that is socially, environmentally, and financially sustainable requires clinical leadership, yet few health-care workers possess the conceptual framework or practical skills for creating new models of care. Clinicians can protect planetary health as a core part of professional practice by integrating triple bottom line measures into quality improvement or quality management practices. Initial efforts to integrate sustainability into quality improvement teaching and training have been shown to transform learners’ interest in quality improvement and environmental sustainability. Embedding sustainability principles and techniques into established quality improvement education and practice can operationalise planetary health, building the skills necessary for health-care system transformation at the speed and scale required.